KONTRIBUSI UNGKAPAN TRADISIONAL DALAM MEMBANGUN KERUKUNAN BERAGAMA - Joko Tri Haryanto (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
The Ganjuran society who live in Sumbermulyo Village, District Bambanglipuro Bantul of DIY, have ability to maintain religious harmony although those people are different religions. It is because Ganjuran society have elements that can be a social glue in their local wisdom. This research is conducted by qualitative approach to reveal local wisdom in the maintaining harmony through the form of traditional expressions and tradition of kenduri (ritual of meal). Ganjuran society has strong social harmony perspective which is expressed by traditional idiom like rukun agawe santosa crah agawe bubrah (harmony makes peaceful, hostile makes splits).